Rapamycin Improves Palmitate-Induced ER Stress/NF κ B Pathways Associated with Stimulating Autophagy in Adipocytes - Jiajing Yin; Liping Gu; Yufan Wang; Nengguang Fan; Yuhang Ma; Yongde Peng (Mediators of Inflammation)
Obesity-induced endoplasmic reticulum (ER) stress and inflammation lead to adipocytes dysfunction. Autophagy helps to adapt to cellular stress and involves in regulating innate inflammatory response. In present study, we examined the activity of rapamycin, a mTOR kinase inhibitor, against endoplasmic reticulum stress and inflammation in adipocytes. An in vitro model was used in which 3T3-L1 adipocytes were preloaded with palmitate (PA) to generate artificial hypertrophy mature adipocytes. Elevated autophagy flux and increased number of autophagosomes were observed in response to PA and rapamycin treatment. Rapamycin attenuated PA-induced PERK and IRE1-associated UPR pathways, evidenced by decreased protein levels of eIF2α phosphorylation, ATF4, CHOP, and JNK phosphorylation. Inhibiting autophagy with chloroquine (CQ) exacerbated these ER stress markers, indicating the role of autophagy in ameliorating ER stress. In addition, cotreatment of CQ abolished the anti-ER stress effects of rapamycin, which confirms the effect of rapamycin on ERs is autophagy-dependent. Furthermore, rapamycin decreased PA-induced nuclear translocation of NFκB P65 subunit, thereby NFκB-dependent inflammatory cytokines MCP-1 and IL-6 expression and secretion. In conclusion, rapamycin attenuated PA-induced ER stress/NFκB pathways to counterbalance adipocytes stress and inflammation. The beneficial of rapamycin in this context partly depends on autophagy. Stimulating autophagy may become a way to attenuate adipocytes dysfunction.